Antecedent of Knowledge of Fatwa, Coronavirus, and Family Factors on Student Compliance with Social Distancing Policies to Reduce the Negative Impact of Covid-19 in Indonesia - Rahmad Hakim; Fadilla Muhammad Mahdi; Adib Susilo; M. Husni Tamrin; Ahmad Fanani; Subhan Mawardi (MIMBAR : Jurnal Sosial dan Pembangunan, 2023)
Abstract. This study aims to determine the effect of knowledge of fatwa, the knowledge of coronavirus disease, and family factors on student compliance with social distancing policies to prevent the spread of Covid-19 in Indonesia. This study was quantitative and the data were collected through questionnaires distributed via google forms. The data were collected from 426 respondents who were students of private and public Universities in Indonesia. The tool of analysis used in this study was the Partial Least Square (PLS) method, a variance-based structural equation analysis (SEM) that can simultaneously perform the measurement and structural model testing. The study found that there was a significant influence of the family factors on the compliance of students with social distancing policies. While there was no significant influence of the knowledge of fatwa and Covid-19 variables on student compliance with social distancing. The results of this study contribute to enriching the discourse of the role of religious and social factors on student compliance with social distancing policy to reduce the spread of Covid-19